THE THE INFLUENCE OF GOOD CORPORATE GOVERNANCE ON PROFIT MANAGEMENT: A CASE STUDY OF SHARIA COMMERCIAL BANKS REGISTERED IN FINANCIAL SERVICES AUTHORITY - Ahliyah, An Nisa’ Sakinatul; Setyaningsih, Nina Dwi (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
Profit is a key indicator of a company's performance, with higher profits reflecting better performance. Management may engage in earnings management to meet profit targets. To mitigate the risks of fraudulent earnings management, effective corporate governance is essential. This study investigates the impact of the board of commissioners' size, independent commissioners, Sharia supervisory board, audit committee, and company size on earnings management. The sample consists of 14 Islamic Commercial Banks registered with the Financial Services Authority from 2013 to 2020, selected using purposive sampling. Hypothesis testing results using the T test reveal that the board of commissioners' size does not significantly impact earnings management (significance level of 0.256). The independent commissioner variable positively and significantly affects earnings management (significance level of 0.000). The Sharia Supervisory Board has no significant impact on earnings management (significance level of 0.964). The audit committee variable also shows no significant effect (significance level of 0.844), and the firm size variable does not affect earnings management (significance level of 0.238)